2021
DOI: 10.1021/acs.jpcc.1c03976
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Structure and Reactivity of Cu and Ag Surfaces in the Formation of a 2D Metal–Hexahydroxytriphenylene Network

Abstract: We have investigated the role played by the atomic structure and reactivity of the supporting Ag(111) and Cu(111) surfaces on the formation of 2D metal–organic networks (2D-MONs) involving metal adatom clusters spawned by these two surfaces. While the hexahydroxytriphenylene (HHTP) molecule forms complexes with Ag3 and Cu3 adatom clusters on, respectively, the Ag(111) and Cu(111) surfaces, an extended order is only observed in the 2D-MON on Ag(111). By combining scanning tunneling microscopy measurements, dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 56 publications
2
15
0
Order By: Relevance
“…While not all the recorded STM images reveal the silver adatoms as clearly discernible features in the HT network (Figure and Figure S6); nevertheless, the evidence provided in Figure and Figure S7 is indicative of a stabilizing N-Ag interaction. Furthermore, it seems a general feature of the Ag adatoms that they tend to be poorly visible, thus elusive, in the STM imaging, as inferred from previous reports. Numerous examples highlight the adatom-induced formation of surface-confined metal-coordination networks, in particular for nitrogen-containing pyridine derivatives. Strikingly, in recent synthetic studies in solution (Supporting Information, Section 10), we also observed the formation of trimetallic Mabiq dimers linked via a central silver atom that bridges two adjoining biquinazoline moieties (Figure S13). This finding provides important evidence for the affinity of the peripheral H-Mabiq site for Ag coordination and the capacity of this metal to bridge two Mabiq units.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…While not all the recorded STM images reveal the silver adatoms as clearly discernible features in the HT network (Figure and Figure S6); nevertheless, the evidence provided in Figure and Figure S7 is indicative of a stabilizing N-Ag interaction. Furthermore, it seems a general feature of the Ag adatoms that they tend to be poorly visible, thus elusive, in the STM imaging, as inferred from previous reports. Numerous examples highlight the adatom-induced formation of surface-confined metal-coordination networks, in particular for nitrogen-containing pyridine derivatives. Strikingly, in recent synthetic studies in solution (Supporting Information, Section 10), we also observed the formation of trimetallic Mabiq dimers linked via a central silver atom that bridges two adjoining biquinazoline moieties (Figure S13). This finding provides important evidence for the affinity of the peripheral H-Mabiq site for Ag coordination and the capacity of this metal to bridge two Mabiq units.…”
Section: Resultssupporting
confidence: 67%
“…The ball-and-stick model presented in Figure and overlaid on the STM image shows that this cavity provides sufficient space to accommodate the Ag adatoms. Indeed, the occurrence of thermally triggered incorporation of Ag adatoms into supramolecular organic networks was recently reported. The presence of Ag adatoms would justify the unusual arrangement of two bulky diketiminate units facing each other, imaged as bright four-lobed protrusions in STM. In contrast, for the RT phase, while similarly large cavities are observed in the self-assembly (Figure a and the tentative ball-and-stick model in Figure S8), we found no STM evidence of adatom incorporation at varying bias.…”
Section: Resultsmentioning
confidence: 97%
“…The modeling of functional extended surfaces has grown in past decades to investigate, for fundamental and engineering purposes, a large number of phenomena or applications such as, e.g., deposition [1], growth and migration [2], 2D assembly [3], catalysis [4], electrocatalysis [5], photocatalysis [6], molecular electronics [7], depollution [8], sensing [9], etc. Many of these studies have focused on deposited clusters, i.e., finite aggregations of basis elements (atoms or molecules) adsorbed on surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of studies have demonstrated the coordination nanostructures by altering organic ligands, such as carboxylate, 3,5,12,18 hydroxyl, 14,20,21 pyridine, 9,22–25 and triazine. 26–30 The triazine derivatives are important in a range of areas as ligands for supramolecular self-assembly of more complex mixed layers, hence it may be interesting to study the coordination properties of the triazine derivatives.…”
Section: Introductionmentioning
confidence: 99%